2008
DOI: 10.1007/s11605-008-0573-0
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Coupled Transport of the Short Chain Fatty Acid Butyrate by SLC5A8 and Its Relevance to Colon Cancer

Abstract: These studies show that SLC5A8 mediates the tumor-suppressive effects of the bacterial fermentation product butyrate in the colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
97
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 31 publications
(47 reference statements)
5
97
1
Order By: Relevance
“…Recently we have shown that propionate, another short-chain fatty acid produced in the colon by bacterial fermentation, is also an inhibitor of HDACs (16). SLC5A8 has been shown to function as a tumor suppressor in the colon (17) and other tissues (13,18,19); the ability of this transporter to mediate the Na ϩ -coupled entry of HDAC inhibitors (butyrate, propionate, and pyruvate) into cells underlies the tumor-suppressive function of this transporter (15,16). While SLC5A8 is necessary for the intracellular actions of butyrate, butyrate also elicits biologic effects on colon cells extracellularly by serving as an agonist for the cell surface G-protein-coupled receptor GPR109A, but without involving HDAC inhibition (20).…”
Section: Dendritic Cells (Dcs)mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently we have shown that propionate, another short-chain fatty acid produced in the colon by bacterial fermentation, is also an inhibitor of HDACs (16). SLC5A8 has been shown to function as a tumor suppressor in the colon (17) and other tissues (13,18,19); the ability of this transporter to mediate the Na ϩ -coupled entry of HDAC inhibitors (butyrate, propionate, and pyruvate) into cells underlies the tumor-suppressive function of this transporter (15,16). While SLC5A8 is necessary for the intracellular actions of butyrate, butyrate also elicits biologic effects on colon cells extracellularly by serving as an agonist for the cell surface G-protein-coupled receptor GPR109A, but without involving HDAC inhibition (20).…”
Section: Dendritic Cells (Dcs)mentioning
confidence: 99%
“…Relevance of Slc5a8 to Butyrate-induced Blockade of DC Development-Slc5a8, a Na ϩ -coupled high-affinity transporter, is essential for the entry of butyrate into cells, particularly at low concentrations, to inhibit HDACs (14,15). To establish the role of Slc5a8 in butyrate-induced blockade of DC development, we examined the effects of butyrate on DC development from Lin Ϫ bone marrow cells from wild-type and Slc5a8 Ϫ/Ϫ mice (Fig.…”
Section: Figure 5 Role Of Hdacs In DC Development a Linmentioning
confidence: 99%
See 1 more Smart Citation
“…Monocarboxylate transporter 1 (MCT1), a member of SLC16 gene family, mediates the H ϩ -coupled transport of butyrate into colonocytes (18,34). Another transporter belonging to SLC5 solute-linked carrier family has recently been characterized as a Na ϩ -coupled transporter of butyrate and, therefore, known as sodium-coupled MCT1 (SMCT1) (16,40). Our laboratory's previous studies demonstrated the role of MCT1 in butyrate transport (18), its membrane localization along the length of the human intestine (15), and its transcriptional or posttranslational modulation by the transcription factor upstream stimulatory factor (17), butyrate (9), PKC- (35), somatostatin (36), and in response to enteropathogenic E. coli infection (7).…”
mentioning
confidence: 99%
“…24,25 For example the butyrate transporter SLC5A8 (SMCT1) gene is commonly silenced epigenetically by aberrant methylation early in human colonic neoplasia 25 , but facilitates butyrate-induced cellular apoptosis when re-expressed in the presence of butyrate. 26 Together these data suggest that the evasion of butyrate-induced apoptosis may be a key step in colorectal oncogenesis. Situations of extensive DNA damage and compromised repair may result in the accumulation of mutations or silencing of repair and apoptotic genes.…”
Section: Discussionmentioning
confidence: 90%